Space Penetration of the Buntet Islamic Boarding School - Chofyan, Ivan; Helena Agustina, Ina; Mukhsin, Dadan; Rosenda, Diden; Yanto, Muhtadin (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
Buntet Islamic Boarding School is the third oldest Islamic boarding school in Indonesia. The Islamic boarding school was founded in 1750 and continues to exist now. It began as a single community in the block of Mertapada Kulon Village and has now grown to include many communities. The penetration of activities in Mertapada Village is interesting to observe in the context of space. Penetration that began with activities that were not economically oriented but developed into economic activities. The early education that was developed was traditional Islamic boarding school education aimed at spreading Islam. The purpose of this study is to explain the penetration space created by the activities of the Buntet Islamic boarding school. This research method combines a spatial approach using an Arch Map with surveys and field observations for ground data checks, interviews, and analysis of descriptions based on map data processing and field surveys, followed by interpretation of spatial penetration caused by Islamic boarding school activities. The study findings show that the Buntet Islamic Boarding School is a hub of activity that is not only focused on education but also on the village community's economic development. Space penetration happens as a result of past experiences and adaptability to the needs of Islamic boarding school education.